2022
DOI: 10.23880/chij-16000136
|View full text |Cite
|
Sign up to set email alerts
|

Uterine Rat Telocyte Structure and Organization: An Immunohistochemical and Ultrastructural Study

Abstract: Telocytes are a kind of interstitial cell found in a variety of organs, including the uterus. They regulate uterine contractions, maintain pregnancy, and prevent premature labour. The purpose of this research was to look at the organisation and distribution of telocytes in different uterine layers in adult and senile rats at various stages of reproduction. Materials & Methods: Twenty-four female rats were evenly divided between four groups: GI: adult non-pregnant, GII … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
(33 reference statements)
1
0
0
Order By: Relevance
“…The endometrium is composed of a simple columnar epithelium situated above the glandular lamina propria, and the myometrium is composed of the inner circular, the middle stratum vascular (SV), and the outer longitudinal layers. Consistent with previous findings, IF results revealed the presence of CD34+/Vimentin+ TCs distributed across all layers of uterine tissue (Es, 2022). Co‐labeling with CD34/Vimentin+ showed that in the endometrium layer, TCs displayed large cellular bodies with long Tps extending around the glands and blood vessels, forming a 3D network structure through homocellular or heterocellular contacts to communication (Figure 1a,b).…”
Section: Resultssupporting
confidence: 91%
“…The endometrium is composed of a simple columnar epithelium situated above the glandular lamina propria, and the myometrium is composed of the inner circular, the middle stratum vascular (SV), and the outer longitudinal layers. Consistent with previous findings, IF results revealed the presence of CD34+/Vimentin+ TCs distributed across all layers of uterine tissue (Es, 2022). Co‐labeling with CD34/Vimentin+ showed that in the endometrium layer, TCs displayed large cellular bodies with long Tps extending around the glands and blood vessels, forming a 3D network structure through homocellular or heterocellular contacts to communication (Figure 1a,b).…”
Section: Resultssupporting
confidence: 91%